Kebijakan Otonomi Daerah Antara Harapan Dan Kenyataan - Deddy Mulyadi (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2005)
For the past five years, implementation of Regional Law No 22/1999 has created distortions and controversy in the govenment management. The objective of establishing democratic, transparant, and accountable local dovernment has not been achievied yet. This condition has called many element of society for the revison of the law, and the result is the Revised Regional Autonomy Law No.34/2004. This essay attempts to discuss several fundamental changes of the Revised Law and impact on the management of local government affairs. One of the changes, according to the law, is that of the local government.